ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN IMUNISASI DASAR PADA BAYI (0-12 BULAN) DI PUSTU DESA TELUK TUASAN WILAYAH KERJA UPT PUSKESMAS SUNGAI ILIRAN TAHUN 2019 - Nursehan; Madinah (Jurnal Kesehatan Husada Gemilang, 2022)
Immunization is an attempt to cause or actively increase a person's immunity to a disease. The achievement of Universal Child Immunization (UCI) in Auxiliary health center of Teluk Tuasan Village 44.67%, this shows it has not reached the national target of 86%. The purpose of this study is to find out the factors that affect the provision of basic immunization in infants (0-12 months) in the Auxiliary health center of Teluk Tuasan Village, Illiran River Health Center in 2019. This research is qualitative descriptive with a phenomenological approach. The study was conducted from July 9 to July 11, 2019. The number of samples of the main informants in this study was 6 people and 6 supporting informants (key informants). The results of the study obtained knowledge, family support, and the number of children affect the provision of basic immunization while the work and affordability of the place of service does not affect the provision of basic immunization. It is expected that the agency where the research can provide counseling to mothers and families about the importance of immunization, as well as the activeness of mothers in Integrated Healthcare Center activities against complete basic immunization in infants, so that the success of immunization programs can be achieved optimally.